Singaporean fighter in IS global strategy : shift from core to periphery - Rohan Gunaratna (2017)
In anticipation of their return to their home countries and regions, IS fighters in Syria and Iraq are calling for global support to strengthen IS bridgeheads in their own regions. For the first time, a Singaporean features in IS propaganda.